Effective school librarianship : successful professional practices from librarians around the world. Vol. 2 - Lo, Patrick; Chiu, Dickson K. W., 1966-; Rogers, Heather, 1990- (Oakville, ON : Apple Academic Press, 2018)
Provides a series of informative interviews with school/teacher librarians from Africa, Asia, and Australia, discussing their creative and innovative school library projects, their unconventional reading programs, and their best practices and experiences in addressing the challenges of supporting basic literacy.
Includes bibliographical references and index.
Adult
Keywords: Library science -- Case studies; School librarians -- Interviews; School libraries -- Administration; Library science -- Case studies; School librarians -- Interviews; School libraries -- Administration; Case studies; Interviews